1995
DOI: 10.1074/jbc.270.26.15620
|View full text |Cite
|
Sign up to set email alerts
|

Domain Closure in the Catalytic Chains of Escherichia coli Aspartate Transcarbamoylase Influences the Kinetic Mechanism

Abstract: The closure of the two domains of the catalytic chains of Escherichia coli aspartate transcarbamoylase, which is critical for completion of the T-->R transition, is stabilized by salt-bridges between Glu-50 and both Arg-167 and Arg-234. Mutation of Glu-50 to Ala shifts the enzyme toward a low activity, low affinity state (Newton, C. J., and Kantrowitz, E. R. (1990) Biochemistry, 29, 1444-1451). Kinetic isotope effects (KIE) and equilibrium isotope exchange kinetics (EIEK) have been used to probe the dynamic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The maximal activity of the C47A/A241C holoenzyme was greater under non-reducing versus reducing conditions (25.6 versus 21 mmol⅐h Ϫ1 ⅐mg Ϫ1 respectively), suggesting that the switch from the T to R state is somewhat rate-limiting in the holoenzyme. This is supported by work done on the wildtype enzyme and D236A, another enzyme with enhanced maximal activity, which suggested that domain closure or "compression," the final step in the T to R transition, is rate-limiting (37,38). There was a significant difference in the nucleotide saturation curves under reducing and non-reducing conditions corresponding to a wild-type-like and R state enzyme, respectively.…”
Section: Discussionsupporting
confidence: 55%
“…The maximal activity of the C47A/A241C holoenzyme was greater under non-reducing versus reducing conditions (25.6 versus 21 mmol⅐h Ϫ1 ⅐mg Ϫ1 respectively), suggesting that the switch from the T to R state is somewhat rate-limiting in the holoenzyme. This is supported by work done on the wildtype enzyme and D236A, another enzyme with enhanced maximal activity, which suggested that domain closure or "compression," the final step in the T to R transition, is rate-limiting (37,38). There was a significant difference in the nucleotide saturation curves under reducing and non-reducing conditions corresponding to a wild-type-like and R state enzyme, respectively.…”
Section: Discussionsupporting
confidence: 55%
“…First, the formation of the high activity high affinity active site, which has ordered substrate binding, requires these interdomain bridging interactions. Without the interdomain bridging interactions, not only does the enzyme lose considerable activity and substrate affinity, but it also exhibits a random rather than an ordered mechanism (11). Second, without these interdomain bridging interactions the enzyme cannot be converted into the R structural state except by the bisubstrate analog, PALA (12).…”
Section: Discussionmentioning
confidence: 99%
“…The kinetic data suggest that the elimination of these interactions prevents domain closure, and, therefore, the high affinity, high activity active site cannot form. Furthermore, in the absence of domain closure, the preferred order substrate binding mechanism is no longer observed; rather the mechanism becomes random (11).…”
mentioning
confidence: 99%
“…Other mutant enzymes, however, are stabilized in the T state. The Glu50cAla enzyme is unable to close the C chain domains and thus does not exist in the R state conformation (58,71). A Thr82rAla enzyme is structurally fixed in an extreme T state with the T-R equilibrium shifted toward the T state (108).…”
Section: Atcasementioning
confidence: 99%